Idiom variability in Croatian: the case of the CONTAINER schema - Parizoska, Jelena (Array, 2009)
In cognitive linguistics most idioms are considered to be motivated by various cognitive mechanisms which link the meaning of the idiom with the meanings of its constituents. One of these mechanisms is the CONTAINER image schema. In Croatian it is reflected in idioms containing the preposition u (‘ in’ ). The CONTAINER schema serves to structure abstract conceptual domains like SITUATIONS, EVENTS and STATES. For example, being in a difficult situation is conceptualized as being in a container. In addition to motivating the idioms with the constituent u, the CONTAINER schema also constrains their variability. This means that variations are not unpredictable, but are dependent on the underlying cognitive mechanism. The aim of the paper is to show that the Croatian idioms describing difficult situations vary their lexico-syntactic structure systematically to reflect the CONTAINER image schema. Based on the data from the Croatian National Corpus, we will show that the idioms share a common element, the construction u + NP, which constitutes the fixed core of each of the expressions and serves as the basis for variant realizations. The lexical and syntactic variations reflect the different ways in which the relation between the trajector (a person) and the landmark (a container-like object) is conceptualized. The variability of the expressions raises the issue of the criteria used in establishing the citation form in monolingual dictionaries of idioms.